Proposal of a Novel Online-Coupling Modular-Structure Maglev Carrier - Bozkurt, Ahmet Fevzi; Erkan, Kadir (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
In the realm of autonomous applications, such as multi-agent drones, swarm ground vehicles, and cooperative/collaborative systems, the concept of modular structures has become increasingly significant. The advantages of modularity include the ability to design more compact agents, leading to reduced manufacturing costs and energy consumption per unit, while simultaneously enhancing operational efficiency. This study introduces a unique modular structure Maglev-based transportation system. The carriers are designed to semi-rigidly couple to each other with a permanent magnet locking structure, allowing two or more carriers to function as a larger structure, resulting in increased payload capacity and providing a fail-safe operational opportunity. This study initiates by introducing a simulation of a multi-agent carrier system operation scenario to showcase the potential of the proposed modular structure compared to a reference model in terms of power consumption. Following this, the analytical force model of MaglevMotor is given, which is subsequently expanded to encompass the dynamic model of the single actuator, single Maglev carrier, and coupled Maglev carrier structure, in order. This progression is accompanied by elucidation on the centralized control method and the extended centralized control method of the coupled model. Consequently, state feedback controller with integral action for each centralized control axis are synthesized for single carrier, and experimental results are provided. Next, the controllers are resynthesized for the coupled structure and proof-of-concept experimental verification for the multi-agent collaborative carrier structure is successfully demonstrated. Finally, online coupling experiments are conducted, and successful results are presented.
Keywords: Force; Payloads; Collaboration; Periodic structures; Centralized control; Analytical models; Transportation; Power demand; Energy consumption; Costs; Collaborative operation; magnetic levitation; modular structure; multi-agent systems; FRAMEWORK; SYSTEM; ROBOTS; Computer Science; Engineering; Telecommunications